Potassium persulfate-glucose mediated synthesis of 3,3′-Bis(indolyl)methanes from arylacetic acid and indoles in water - Indurthi H.K.; Das S.; Saha P.; Koli S.N.; Sharma D.K. (My University, 2025)
An efficient and eco-friendly method has been developed for the preparation of 3,3′-bis(indolyl)methanes from indoles and aryl acetic acid is reported. The in-situ conversion of aryl acetic acid to their corresponding carbonyl compounds, and subsequent condensation with indoles was prompted by K2S2O8 in presence of glucose in water. The metal-free reaction with room temperature conditions, and wide substrate scope with good functional group tolerance are the salient features of the developed methodology. © 2024 Elsevier B.V.